Student-centered learning strategy : the effectiveness of scientific notebook software on students' comprehension in learning integration - Ab Hamid, M. R.; Abdullah, Ibrahim (2006)
The purpose of this research is to evaluate the effectiveness of learning module called LISNoS (Learning Integration using Scientific Notebook Software) that was developed in Scientific Notebook Software using the ADDIE model of instructional design. The instructional approach embedded is the constructivism theory of learning through guided approach. There were 46 students involved in the study at the Faculty of Civil and Environmental Engineering, KUKTEM and they were assigned into two groups i.e. experimental group who use LISNoS and control group who follow traditional teaching method. After going through six hours of teaching and learning process, students in both groups sat for the Integration Test for measuring the procedural skills and transfer skills. Closed-ended questionnaires were distributed only to students in the experimental group and ten of them also were randomly chosen for answering the open-ended questionnaire. These two types of questionnaire were meant to observe students' opinion quantitatively and qualitatively towards the use of LISNoS in the teaching and learning process. Students' achievement in the Integration Test was analyzed using T Test. Data from closed-ended questionnaire was analyzed using mean analysis whilst the data from the open-ended questionnaire was meant to obtain students' opinions subjectively. From the findings, it revealed that students in the experimental group performed better compared to students in the control group and using T Test analysis, there was a significant difference between the two groups in the Integration Test at p<0.05. This finding also showed that experimental group students acquired good procedural skills and transfer skills and their opinions towards the use of LISNoS were positive and encouraging. In conclusion, the LISNoS has a potential in enhancing students' performance in learning Integration but nevertheless, there is still a lot room for improvements in the learning module and the research may further be extended to other topics and study on the acquisition of problem solving skills based on Polya model.